Are pediatric group visits effective for the treatment of obesity?. Issue 8 (August 2016) - Ward, Meghan; Russell, Helena; Maples, Sarah; McCarthy, Catherine
Abstract : Evidence‐Based Answer : No. Ambulatory group visit settings have not been shown to have any significant effects on decreasing body mass index (BMI) in obese pediatric patients. Inpatient group visits are effective while continued, but all effects are gone by 18 months after discharge (SOR: B, RCTs).